Teacher- and student-related factors supporting primary school students' self-regulated learning - Matulaitienė, Jovita; Kaminskienė, Lina; Monkevičienė, Ona; Lehtinen, Erno (Frontiers in Education, 2025)
This study investigates how teachers' strategies and learners' behavior contribute to the development of self-regulated skills (SRL) in primary education. The development of SRL in this level of education is not well investigated, yet SRL skills are important indicators of students' success in later years of their studies. The study responds to the scientific and practical problem related to the fact that teachers are not sufficiently familiar with the teaching of SRL in the classroom. The article is based on the data gained from self-reported questionnaires on SRL development for fourth graders (n = 253) and their class teachers (n = 16) in Lithuania. Multiple regression analysis was used to analyse the survey data and to identify the interaction relationships between the participants. Four main predictors of the development of SRL skills in primary education were identified including teachers' attitudes toward teaching, teachers' support strategies for students, learning environment and students' perceived teacher support. The results indicate that students' perceived teacher support and learning situations modeled by teachers through the learning environment significantly impact the development of SRL skills in primary education.